Calcium ionophoretic activity of chemically synthesized oligomeric derivatives of prostaglandin B1 - Uribe, Salvador; Ohnishi, S.Tsuyoshi; Israelite, Craig; Devlin, Thomas M. (Biochimica et biophysica acta, 1987)
Chemically synthesized dimers, trimers and tetramers of 15-dehydroprostaglandin B1 and 16,16'-dimethyl-15-dehydroprostaglandin B1 facilitate the release of Ca2+ from isolated rat liver mitochondria. The parent monomeric prostaglandins had no significant activity. The rate of release was stimulated by exogenous K+ or Na+, suggesting an antiport exchange of monovalent cations for intra-mitochondrial Ca2+. The activity depended upon the presence of ruthenium red, which prevented recycling of Ca2+; comparison of the activity with A23187 and carbonyl cyanide p-trifluoromethoxyphenylhydrazone indicated that the prostaglandin B1 oligomers were functioning as ionophores and the release of Ca2+ was not caused by an uncoupling of oxidative phosphorylation. The oligomers caused a major decrease in the membrane potential but only when the mitochondria were preloaded with exogenous Ca2+, and even then, the Ca2+ efflux was completed before the membrane potential decreased to less than 90 mV. The oligomeric molecules were able to form supramolecular aggregates in the presence of Ca2+ as detected by light scattering. They extracted Ca2+ into an organic phase, and translocated Ca2+ from one aqueous domain to another across an organic barrier; K+ and Na+ modulated these processes. The prostaglandin B1 derivatives also translocated Rb+ from one aqueous phase to another across an organic barrier when Ca2+ was translocated.